TAPPING THE STRENGHT OF CONCRETE WASTE: ENHANCING COMPRESSIVE AND FLEXURAL STRENGHT THROUGH COARSE AGGREGATE SUBSTITUTION IN NORMAL CONCRETE - Herly Rizki Firmansyah; Sun Tong (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2025)
It is urgently needed a construction technology that can reduce natural exploitation and can utilize concrete wastes. One example of an effort to reduce this impact is to reuse waste concrete for new concrete. This study aims to determine how much influence concrete waste as a substitute for coarse aggregate has on compressive strength and flexural strength. This study plans normal concrete with a targeted compressive strength of 20 MPa and uses 60-180 mm slump and uses Portland Pozzolan Cement (PPC). The proportion of waste aggregate used in this study was 0%, 5%, 7.5%, 10% and 12.5% of the total weight of natural aggregate with a test age of 7 days, 14 days and 28 days. The number of test objects is 60 pieces. The compressive strength and flexural strength results will be compared with the 0% variation. The results of this study indicate that the greater the percentage of concrete waste, the compressive strength and flexural strength of concrete decreases. The compressive strength of concrete and the flexural strength of concrete with variations of concrete waste substitution obtained the optimum percentage in the compressive strength test, namely in the 5% waste concrete substitution with a value of 18.18 MPa, and in the flexural strength test of concrete the optimum percentage is found in the 5% substitution variation with a value of 3.385 Mpa